Unexpected acute appendicitis found at laparoscopic surgery for a right ovarian teratoma: A case report - Rie Okuya; Hiroshi Ishikawa; Nozomi Sakai; Eri Katayama; Kaori Kuroda; Kaori Koga (Case Reports in Women's Health)
Acute appendicitis and adnexal torsion associated with ovarian tumors are possible causes of acute abdomen in women, yet differentiation remains challenging. Once adnexal torsion is suspected in young women, gynecologists should perform surgery to release the torsion as promptly as possible to preserve future fertility. Herein, we report a case of acute appendicitis that was unexpectedly discovered during laparoscopic surgery initially performed for suspected torsion of a right ovarian teratoma. A 20-year-old nulligravid woman with a history of left ovarian teratoma resection and ulcerative colitis presented with left lower abdominal pain. Non-contrast-enhanced computed tomography showed no findings suggestive of exacerbation of ulcerative colitis, such as bowel wall thickening or worsening ascites, while a mass suspected to be an ovarian teratoma was identified. Gynecologists and an emergency physician specializing in gastroenterology who attended the patient suspected an acute abdomen caused by adnexal torsion or tumor leakage associated with a right ovarian teratoma 5 cm across. However, laparoscopy revealed that the right ovarian teratoma was neither twisted nor ruptured. Instead, the appendix was swollen with yellow turbid ascites, compatible with acute appendicitis. Therefore, laparoscopic excision of the right ovarian teratoma and appendix was performed, and the patient's pain resolved postoperatively. The assumption that the pain was caused by torsion of the right ovarian teratoma was the primary reason for failing to diagnose acute appendicitis. This underscores the importance of evaluating the appendix during gynecologic laparoscopic surgery performed for suspected ovarian torsion.